Russian and Foreign Experience of Placement for Orphans - M. Bronnikova, Evgeniya (2020)
Children are the main value of the country, they need care and special attention. The government is obliged to ensure the implementation of children's rights to upbringing, education and development. The family education of children is the priority form. However, there is a problem of orphanage and social orphanage, children left without parental care. There are various forms of placement for orphans. The family form of the placement, foster families, are priority in the world.